The practice of informed consent...this article originally appeared in Urologic Nursing, 24(6), 513-515 and is reprinted here with the permission of the publisher - Quallich SA (Dermatology Nursing, 2005)
Informed consent is the legal doctrine that every adult individual has the right to decide what can and cannot be done to his/her person; this is the issue of autonomy. As the health care environment becomes increasingly litigious, and as patients can obtain information freely via the Internet, understanding the specific components of informed consent becomes vital.